Study on Strength Characteristics of Solidified Contaminated Soil under Freeze-Thaw Cycle Conditions - Qiang Wang; Jinyang Cui (Advances in Civil Engineering)
Cement solidification/stabilization is a commonly used method for the remediation of contaminated soils. The stability characteristics of solidified/stabilized contaminated soils under freeze-thaw cycle are very important. A series of tests, which include unconfined compressive strength tests, freeze-thaw cycle tests, and scanning electron microscopy (SEM) tests, are performed to study the variation law of strength characteristics and microstructure. It aims at revealing the microcosmic mechanism of solidified/stabilized Pb2+ contaminated soils with cement under freeze-thaw cycle. The results show that the unconfined compressive strength of the contaminated soils significantly improved with the increase of the cement content. The unconfined compressive strength of stabilized contaminated soils first increases with the increase of times of freeze-thaw cycle, and after reaching the peak, it decreases with the increase of times of freeze-thaw cycle. The results of the scanning electron microscopy tests are consistent with those of the unconfined compressive strength tests. This paper also reveals the microcosmic mechanism of the changes in engineering of the stabilized contaminated soils under freeze-thaw cycle.